Hydrogel assistant synthesis of new Ti-MOF cross-linked oxidized pectin and chitosan with anti-breast cancer properties - Alkhathami, Ali G.; Khaled Younis Albahadly, Waleed; Jawad, Mohammed Abed; Ramadan, Montather F.; Alsaraf, Khulood Majid; Riyad Muedii, Zainab Al-Hawraa; Alsaikhan, Fahad; Suliman, Muath (Frontiers in Materials, 2023)
Breast cancer is one of the most common diseases of the modern age. Although many methods for its treatment have been reported so far, the report and synthesis of new compounds based on new technologies, especially nanotechnology, is important. One of the laboratory methods for evaluating the anticancer properties of compounds is the in vitro MTT method (3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide). In this study, the in vitro anti-breast cancer activity of the newly synthesized (Titanium Metal-Organic Framework) Ti-MOF cross-linked oxidized pectin and chitosan hydrogel, which uses biopolymers in its synthesis and structure, was investigated. The anticancer activity results showed that the synthetic nanopolymer had cell proliferation and viability of 27% more than the control and (the half maximal inhibitory concentration) IC50 of 111 μg/mL against breast cancer cells. Before the anticancer evaluation, the structure of the synthesized Ti-MOF cross-linked oxidized pectin, and chitosan hydrogel was confirmed by (X-Ray Diffraction) XRD pattern (Fourier Transform Infrared) FT-IR spectrum (Energy-dispersive X-ray) EDAX spectroscopy, N2 adsorption/desorption isotherm and (Scanning Electron Microscope) Scanning Electron Microscope images. The results of identification and characterization showed that the synthetic nanopolymer was in the range of nanoparticles. The peaks of the expected functional groups and reactant elements were observed in the FT-IR spectrum and energy-dispersive X-ray spectroscopy of the final product. High physicochemical capabilities such as the uniform morphology, crystallization of particles, and high specific surface area from synthesized Ti-MOF cross-linked oxidized pectin, and chitosan hydrogel were observed. The unique properties of the synthesized Ti-MOF cross-linked oxidized pectin and chitosan hydrogel can be attributed to the appropriate method of its synthesis that was carried out in this study.